Association between ACTN3 R577X Polymorphism and Trunk Flexibility in 2 Different Cohorts - Kikuchi, Naoki; Zempo, Hirofumi; Fuku, Noriyuki; Murakami, Haruka; Sakamaki-Sunaga, Mikako; Okamoto, Takanobu; Nakazato, Koichi; Miyachi, Motohiko (International Journal of Sports Medicine, 2017)
α-Actinin-3 (ACTN3) R577X polymorphism is associated with muscular strength and power. This study was performed to investigate the association between ACTN3 R577X polymorphisms and flexibility as another component of fitness in 2 cohorts. Cohort 1 consisted of 208 men and 568 women (ages 23–88), while Cohort 2 consisted of 529 men and 728 women (ages 23–87). All participants were recruited from the Tokyo metropolitan area and underwent a battery of tests to assess their grip strength and sit-and-reach flexibility. Genotyping results were analyzed for ACTN3 (rs1815739) polymorphism using the TaqMan approach. In Cohort 1, sit-and-reach in the RR genotype (35.3±0.7 cm) was significantly lower than those in the RX and XX genotypes (37.2±0.3 cm) even after adjusting for sex, age, and exercise habit as covariates (P<0.01). In Cohort 2, sit-and-reach tended to be lower in RR (38.1±0.6 cm) than in RX and XX (39.1±0.3 cm), but the differences were not significant (P=0.114). Analysis in pooled subjects indicated that RR was associated with significantly lower flexibility than RX and XX (P=0.009). The RR genotype of ACTN3 R577X in the general Japanese population showed lower flexibility compared to the RX and XX genotypes.
Keywords: α-actinin 3; genotype; sit-and-reach; meta-analysis